Implementasi Pengendalian Risiko Kebisingan Dengan Pendekatan Hirarki Pengendalian Di Bagian Proses Pt. Iskandar Indah Printing Tekstil Surakarta - ANGGORO , DANANG KURNIAWAN (2012)
The measurement result of noise intensity at the process is over the threshold value, that is 100,23 dB. So it is necessary to do something to control the noise with hierarchy of controlled approachment. The goal of the research is about to know implementation of noise risk control by controlled hierarchy approachment in process department. This research is a kind of descriptive research and using the survey method. The subject of this research is management, supervisor, and the employees in the process department. The noise is measured with Sound Level Meter. The identification of noise source on the 632 machines in the process department is over the noise threshold value that has been determined. The danger of noise in the process department has a high or serious risk. The implementation of the noise danger management that have been done with the danger management hierarchy technique, such as: technique engineer, administration, and self-protector tools. Based on the data analyze result, the noise management with the technique engineer method, administration, and self-protector tools are not effective yet to c ontrol the noise in the process department of PT. Iskandar Indah Printing Tekstil. The firm is advised to provide ear muff for all of the employees to temporary controlled and form the long term for the K3 board.